2012
DOI: 10.1103/physrevd.85.054019
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark production inγPinteractions at hadronic colliders

Abstract: The diffractive heavy quark cross sections are estimated considering photon-Pomeron (γIP ) interactions in hadron -hadron at RHIC, Tevatron, and CERN LHC energies. We assume the validity of the hard diffractive factorization and calculate the charm and bottom total cross sections and rapidity distributions using the diffractive parton distribution functions of the Pomeron obtained by the H1 Collaboration at DESY-HERA. Moreover, we compare our predictions with those obtained using the dipole model. We verify th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…For a similar analysis of charm and bottom production in γP and PP interactions see, e.g., Refs. [23][24][25]. Our predictions for the tt production could potentially be sensitive to the Pomeron gluon distribution at large values of β and μ 2 , beyond the kinematical range probed by HERA.…”
Section: Formalismmentioning
confidence: 86%
“…For a similar analysis of charm and bottom production in γP and PP interactions see, e.g., Refs. [23][24][25]. Our predictions for the tt production could potentially be sensitive to the Pomeron gluon distribution at large values of β and μ 2 , beyond the kinematical range probed by HERA.…”
Section: Formalismmentioning
confidence: 86%
“…Refs. [2][3][4]). Recent experimental results from CDF [5] at Tevatron, STAR [6] and PHENIX [7] at RHIC and ALICE [8] and LHCb [9] at LHC have demonstrated that the study of coherent interactions in these colliders is feasible and that the data can be used to constrain the description of the hadronic structure at high energies.…”
Section: Introductionmentioning
confidence: 99%
“…It can be obtained by the convolution of the Pomeron flux f IP (x IP ) and the gluon distribution in the Pomeron g IP (ȕ, 2 ), as showed at [1]. The cross section for the photon-gluon fusion is given at leading order by…”
Section: Resultsmentioning
confidence: 99%